The solidarity economy alternative and movement: The experience of the United States Solidarity Economy Network (USSEN) - Esteves, A. (The solidarity economy alternative: Emerging theory and practice, 2014)
The solidarity economy movement in the US is very recent. While use of this term as a framework for unifying the wide array of people-centred economic concepts and practices started in Canada in the mid- to late 1990s, it only became part of the US lexicon in the mid-2000s (Poirier and Kawano 2009: 145). The US solidarity economy movement took shape with the establishment of the United States Solidarity Economy Network (USSEN) at the First US Social Forum (USSF), held in Atlanta, Georgia, in June 2007. However, it builds on a broad range of pre-existent economic practices, institutions and policies representing alternatives to capitalist production (Allard 2008b). The environmental crisis and the recurring economic turmoil in recent decades have led to a rising interest in these alternatives.